Alcohol use, alcohol‐related aggression and intimate partner abuse: A cross‐sectional survey of convicted versus general population men in Scotland. (January 2017) - Gilchrist, Elizabeth Allison; Ireland, Lana; Forsyth, Alasdair; Godwin, Jon; Laxton, Tim
Abstract: Introduction and Aims: Scotland has a particular problem with alcohol, and the links between intimate partner abuse (IPA) and alcohol appear stronger here than elsewhere across Europe. This study explored differences in alcohol use, related aggression and relationship conflict across a number of groups: men convicted for intimate partner abuse, men convicted of general offences and men recruited from community sports teams. Design and Methods: Participants (n = 64) completed three questionnaires exploring their experiences of alcohol use (Alcohol Use Disorders Identification Test, AUDIT); alcohol and aggression (Alcohol Related Aggression Questionnaire, ARAQ‐28), and relationship conflict (Revised Conflict Tactics Scale, CTS‐2). Results: There were significant differences across the groups in terms of AUDIT and ARAQ‐28 scores, IPA and general offenders scored higher than the community sample. CTS‐2 scores showed significant differences: both offender groups reported more use of negotiation and psychological abuse, than the community men, and IPA offenders reported causing more physical harm than either general offenders or the community sample. ARAQ‐28 scores correlated with psychological abuse for general offenders. Alcohol use was very high across all groups, but the community group did not endorse an aggression‐precipitating view of alcohol and did not report high IPA. Discussion and Conclusions: Discussed is the need for cross‐cultural research to explore putative mediators and moderators in the relationship between alcohol, aggressiveness and IPA. [Gilchrist EA, Ireland L, Forsyth A, Godwin J, Laxton T. Alcohol use, alcohol‐related aggression and intimate partner abuse: A cross‐sectional survey of convicted versus general population men in Scotland. Drug Alcohol Rev 2017;36:20–23]